2015
DOI: 10.1080/02791072.2015.1102991
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Exercise for the Quality of Life of Drug-Dependent Patients

Abstract: This study combined quantitative and qualitative research methods to evaluate quality-of-life changes in drug-dependent patients after participation in a group-based exercise program. Quality of life (SF-36) and physical fitness (six-minute Walk Test, Timed Get Up and Go Test, and Chair Stand Test) were quantitatively determined in a group (n=37) of drug-dependent patients before and after a 12-week group exercise program (n=18) or routine care (n=19). Additionally, in-depth interviews were conducted at the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
2
27
1
1
Order By: Relevance
“…Although no studies have investigated the effects of core stabilization exercise on the 6MWT distance in patients with SUD, the current study observed that the 6MWT distance was significantly improved in the exercise group (+ 65 m) and the control group (+24 m). Contrary to Gimenez‐Meseguer et al, the control group in the present study showed a significant improvement in 6MWT distance because they participated in recreational activities in addition to the usual care. On the other hand, there was less improvement in the 6MWT distance of the exercise group (+65 m) in our study compared with that of Gimenez‐Meseguer et al (+167 m), which may be due to the duration of the exercise training.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although no studies have investigated the effects of core stabilization exercise on the 6MWT distance in patients with SUD, the current study observed that the 6MWT distance was significantly improved in the exercise group (+ 65 m) and the control group (+24 m). Contrary to Gimenez‐Meseguer et al, the control group in the present study showed a significant improvement in 6MWT distance because they participated in recreational activities in addition to the usual care. On the other hand, there was less improvement in the 6MWT distance of the exercise group (+65 m) in our study compared with that of Gimenez‐Meseguer et al (+167 m), which may be due to the duration of the exercise training.…”
Section: Discussioncontrasting
confidence: 99%
“…There is only one study in the literature that investigated the effects of exercise training on functional capacity in patients with SUD. In this study, Gimenez‐Meseguer et al reported that a 12‐week aerobic exercise program significantly improved the 6MWT distance in the experimental group (+167 m), but there was no statistically significant improvement in the control group (−11 m). Although no studies have investigated the effects of core stabilization exercise on the 6MWT distance in patients with SUD, the current study observed that the 6MWT distance was significantly improved in the exercise group (+ 65 m) and the control group (+24 m).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Specific physical benefits, indicated by reductions in injuries and muscular pains, decreased weight, and increased vitality with the development of necessary activities of daily living, psychological benefits (i.e. forgetting about everyday problems, improved mood, decreased stress and anxiety), social benefits, and a reduction in craving were estimated through qualitative measures [ 26 ]. In the “STimulant Reduction Intervention” program, carried out over nine residential addiction treatment initiatives (USA), a dosed exercise STRIDE intervention increased the mean percentage of abstinence days and levels of abstinence rates among participants [ 27 , 28 ].…”
mentioning
confidence: 99%
“…Although exercise is not typically a component of current treatment programs, individuals with SUDs are interested in engaging in exercise as part of their treatment to help reduce substance cravings and boredom and, to improve their overall physical and mental health (Abrantes et al, ; Gimenez‐Meseguer, Tortosa‐Martinez, & de los Remedios Fernandez‐Valenciano, ; Neale, Nettleton, & Pickering, ). Many adults with SUDs have expressed the preference to begin an exercise program early in their recovery (within the first 3 months) (Abrantes et al, ; Neale et al, ).…”
Section: Treatment Programs For Substance Use Disordersmentioning
confidence: 99%